Variable VAR compensator circuits - El-Habrouk, Mohamed; Darwish, Mohamed K.; Marouchos, Christos (My University, 2006)
A family of two reactive-power compensator circuit is presented. A general model of some basic linear elements and switching function blocks is developed first. Then the two proposed compensator circuits are derived from the generalised model. The proposed circuits are capable of supplying leading as well as lagging reactive currents in stepless variation without using an inverter configuration. The switching frequency is in the range of 2.5kHz and the largest capacitor utilised does not exceed 60μF. The generated reactive current, in either the leading or lagging modes, contains less than 2 total harmonic distortion.
Keywords: Electric currents; Electric inverters; Reactive power (Electrical engineering); Switching circuits